Carbon stocks and footprints of smallholder cacao systems in Polewali Mandar, West Sulawesi - Miharza, Try; Wijayanto, Nurheni; Roshetko, James M.; Siregar, Iskandar Zulkarnaen (Frontiers in Environmental Science, 2023)
Cacao (Theobroma cacao) is a commodities that plays an important role in supporting economic and social development. However, cacao can also be a major contributor of carbon emissions, which has stimulated various efforts toward sustainable cacao farm management. There remains a gap in knowledge regarding the links between carbon stocks and carbon footprints, which can serve as indicators of environmental ‘friendliness’. In this study, we investigated carbon stocks and carbon footprints in two cacao cultivation systems, agroforests and monocultural systems and the biophysical aspects (biotic and abiotic factors) that might contribute to variability of carbon levels. The results show that cacao agroforests accumulated more carbon stocks than cacao monocultures, namely 134.43 Mg C ha-1 and 104.7 Mg C ha-1, respectively; while cacao monocultural systems had higher carbon footprints than cacao agroforests, 1914.4 kg CO2e ha-1 and 932.1±251.6 kg CO2e ha-1, respectively. Canopy cover, trees density, and soil organic carbon were biophysical aspects that showed significant positive correlation with carbon stock levels, while canopy cover had a significantly negative correlation with carbon footprint levels. These results suggest that cacao agroforests are climate-friendly management systems due to their ability to maintain high carbon stock levels while producing low carbon footprints.